You're not the boss of me : brat-proofing your 4- to 12-year-old child - Braun, Betsy Brown (Harper, 2010)
A guide for parents of children between the ages of four and twelve presents advice on dealing with difficult behavior and provides strategies to help children become more self-reliant, show gratitude, be respectful of others, and take personal responsibility.